Prevalence of vulvovaginal candidiasis in Brazil: A systematic review - Carvalho, Gabriela Corrêa [UNESP]; De Oliveira, Rafaela Aparecida Prata [UNESP]; Araujo, Victor Hugo Sousa [UNESP]; Sábio, Rafael Miguel [UNESP]; De Carvalho, Lídia Raquel [UNESP]; Bauab, Taís Maria [UNESP]; Corrêa, Ione [UNESP]; Chorilli, Marlus [UNESP] (Oxford University Press (OUP), 2021)
Vulvovaginal candidiasis (CVV) is a condition in which signs and symptoms are related to inflammation caused by Candida spp infection. It is the second leading cause of vaginitis in the world, representing a public health problem. The present systematic review comes with the proposal of analyze and identify the available evidence on CVV prevalence in Brazil, pointing out its variability by regions. For this, a systematic literature review was carried out with meta-analysis of cross-sectional and cohort studies, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) guide recommendations, and was registered in the International Prospective Register of Systematic Reviews (PROSPERO 2020 CRD42020181695). The databases used for survey were LILACS, Scielo, Scopus, PUBMED, Web of Science and CINAHL. Fifteen studies were selected to estimate CVV prevalence in the Brazilian territory. South and Southeast regions have higher prevalences than the North and Northeast regions, no data were found for the Midwest region. The estimated prevalence for Brazil is 18%, however, it is suggested that this number is higher due to underreporting and the presence of asymptomatic cases. Therefore, new epidemiological studies are recommended throughout Brazil, to elucidate the profile of this disease in the country, in addition to assisting in the elaboration of an appropriate prevention plan by state. Lay summary: Data found in the literature regarding the epidemiological profile of vulvovaginal candidiasis in Brazil are obsolete and incomplete, so the present systematic review has the proposal to analyze and identify the evidence on vulvovaginal candidiasis prevalence in Brazil. The estimated prevalence is 18%; however, this number can be higher.
Keywords: Brazil; Candida spp; prevalence; vaginitis; vulvovaginal candidiasis